Dupilumab as Immunomodulatory Rescue for Severe Recalcitrant Pemphigus Vulgaris: A Case Report and Literature Review - Boonpethkaew S; Chanprapaph K (Clinical, Cosmetic and Investigational Dermatology, 2025)
Suphagan Boonpethkaew, Kumutnart Chanprapaph Division of Dermatology, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, 10400, ThailandCorrespondence: Kumutnart Chanprapaph, Division of Dermatology, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, 10400, Thailand, Tel +66 22011141, Email kumutnartp@hotmail.comAbstract: Standard treatment of pemphigus vulgaris (PV) includes corticosteroid, immunosuppressants, and biologics such as rituximab, a monoclonal antibody targeting CD20+ B cells. However, some patients develop resistance to rituximab, requiring alternative therapeutic approaches. We report a 15-year-old female with severe PV who developed rituximab refractoriness after an initially effective response. Despite treatment with a combination of intravenous immunoglobulin, corticosteroid, and immunosuppressants, the patient failed to achieve disease control. Consequently, dupilumab, an interleukin-4 receptor α antagonist, was initiated on a biweekly regimen. Her lesions showed dramatic improvement, with the pemphigus disease area index (PDAI) reaching 0. Her anti-desmoglein 1 antibody level became negative, and T helper (Th)-2 inflammatory markers, including eosinophil count and immunoglobulin E (IgE) level, was normalized, allowing corticosteroid tapering after the 8th dose (last dose) of dupilumab. She has maintained complete remission for at least 28 weeks with regular follow-ups. We additionally propose possible mechanisms underlying rituximab refractoriness and how dupilumab modulates this treatment response. Our case highlights dupilumab’s potential in modulating Th-2-driven autoantibody production for PV patients with high peripheral eosinophils and IgE levels who have severe disease resistant to corticosteroids or rituximab.Plain Language Summary: This is a report on a case with severe pemphigus vulgaris (PV) unresponsive to rituximab (anti-CD20) and successfully treated with dupilumab (anti-IL4Rα), suggesting a potential role for dupilumab in severe recalcitrant PV.Keywords: pemphigus vulgaris, bullous disease, autoimmune disease, dupilumab, type 2 immune response, rituximab